Apology and Spanish Criminal Law at the Post-Sentencing Level: the Gap Between Legal Provisions and Victims and Offenders’ Experiences in Cases of Terrorism - Varona, Gema (Oñati Socio-Legal Series, 2017)
This paper deals with the Spanish provisions in criminal law requesting apology by offenders in organized crime, including terrorism. In order to grant parole, apology is required, among other possible means provided by law, to accredit the abandonment of the ends and means of the terrorist activity. Those legal provisions will be contrasted with the experience and narratives of victims and offenders in cases of terrorism. Final conclusions will be derived in relation to the possibility of restorative apologies in these contexts.